On the methodology of the handling of waste - Коваленко, Олексій Михайлович (Eastern-European Journal of Enterprise Technologies, 2011)
The article presents an analysis of the waste problem in Ukraine, considered its environmental, economic and social aspects. Identified problems and proposed solutions to issues connected with the waste of the production and the consumption